Book Review - India’s External Commercial Borrowing : Features, Trends, Policy, and Issues - Ramachandran, P. P. (Indian Journal of Finance, 2022)
The book, India’s External Commercial Borrowing: Features, Trends, Policy, and Issues gives a multi-faceted view of India’s external commercial borrowing and throws a flood of light on it. It discusses the features and pertinent issues in India’s external debt management, focusing on ECB with comprehensive analysis and making recommendations for policy framework. The scholarly prowess of the author is reflected in the concise and lucid presentation. The book will be useful for students, business persons, researchers, and CFOs. About the Author, Dr. Ashutosh Raravikar : Director, DEPR, Reserve Bank of India. He also worked as Director at the Ministry of Finance, Government of India. Rich educational and scholarly background, gold medallist. Eminent economist, central banker, and author with a contribution to international fora. Winner of several prestigious awards. Versatile personality - educationist, spiritualist, literary writer, popular speaker, classical singer